The Effects of Different Irrigation Techniques on Wheat Growth and Yield under Paktia Province’s Climatic Conditions - Ahmadzai, Mohammad Amin; Ahmadzai, Mohammad Dawod; Juyan, Ahmadullah (Journal of Natural Sciences – Kabul University, 2024)
Wheat (Triticum aestivum L.) is one of Afghanistan's most cultivated cereal crops. While much of Afghanistan's soil is suitable for wheat cultivation, limited water resources have significantly hindered agricultural productivity. In arid and semi-arid regions, wheat growth and yield largely depend on annual precipitation. This study was conducted during the years 1401–1402 (2022–2023) at the research farm of Paktia University to determine the impact of different irrigation techniques on wheat growth and yield. The findings revealed that the furrow irrigation system had a significant positive effect on wheat growth and yield. Statistical analysis indicated that wheat yield increased to 2,130 kg per hectare under the furrow irrigation technique, compared to the lowest yield of 1,450 kg per hectare in the control treatment. The weight of 1,000 grains was recorded at 30.2 grams under the traditional irrigation system, while it increased to 38.1 grams using the furrow irrigation technique. Additionally, the furrow irrigation method increased wheat spike length by 30% compared to the conventional system.